Bactericidal and catalytic performance of green nanocomposite based-on chitosan/carbon black fiber supported monometallic and bimetallic nanoparticles. (December 2017) - Ali, Fayaz; Khan, Sher Bahadar; Kamal, Tahseen; Anwar, Yasir; Alamry, Khalid A.; Asiri, Abdullah M.
Abstract: Nanoparticles were synthesized on the surface of green nanocomposite based on carbon black dispersed in chitosan (CB–CS) fibres. The nanoparticles were monometallic Co, Ag and Cu and bimetallic Co + Cu and Co + Ag. The CB–CS fibres were prepared and introduced into separate metal salt solutions containing Co 2+, Ag + and Cu 2+ and mixed Co 2+ +Cu 2+ and Co 2+ +Ag + ions. The metal ions immobilized on the surface of CB–CS were reduced using sodium borohydride (NaBH4 ) as reducing agent to synthesize the corresponding zero-valent metal nanoparticles-loaded CB–CS fibres. All the nanoparticles-loaded CB–CS samples were characterized using field emission-scanning electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction techniques. When tested as catalysts, the nanoparticles-loaded CB–CS showed excellent catalytic ability for the reduction of toxic and environmentally unwanted pollutants of para -nitrophenol, congo red and methyl orange dyes. Afterwards, the antimicrobial activities of virgin and metal-loaded CB–CS fibres were tested and the metal-loaded CB–CS fibres were found to be effective against Escherichia coli . In addition, the catalyst can be recovered easily by simply removing the fibres from the reaction mixture and can be recycled several times while maintaining high catalytic efficiency. Graphical abstract: Highlights: Carbon-black/chitosan fibers (CB–CS) supported mono- and bi-metallic nanoparticles (NPs) were prepared. The successful preparation of the material was confirmed by different characterization methods. CB-CS fibers supported metal NPs catalysed the reduction of toxic para- nitrophenol and azo dyes. The bimetallic Co + Cu/CB–CS showed highest catalytic performance among all the tested catalysts. All the CB-CS fibers supported metal NPs showed strong antimicrobial property.